2015
DOI: 10.5194/angeo-33-1195-2015
|View full text |Cite
|
Sign up to set email alerts
|

The latitudinal structure of the nightside outer magnetosphere of Saturn as revealed by velocity moments of thermal ions

Abstract: Abstract. In this study we investigate the latitudinal behavior of the azimuthal plasma velocities in the outer magnetosphere of Saturn using the numerical ion moments derived from the measurements of the Cassini Plasma Spectrometer. One of the new results presented is that although these moments display some scatter, a significant positive correlation is found to exist between the azimuthal velocity and the plasma density, such that on average, the higher the density the higher the rotation speed. We also fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The plasma density changes smoothly in the region in question, in accordance with an initially exponential falloff. There are no detectable boundaries where the magnetospheric plasma abruptly disappears (see Nemeth et al 2015). Thus the behavior of the thermal plasma supports the notion that these are indeed closed-field vortices.…”
Section: Datasupporting
confidence: 64%
See 2 more Smart Citations
“…The plasma density changes smoothly in the region in question, in accordance with an initially exponential falloff. There are no detectable boundaries where the magnetospheric plasma abruptly disappears (see Nemeth et al 2015). Thus the behavior of the thermal plasma supports the notion that these are indeed closed-field vortices.…”
Section: Datasupporting
confidence: 64%
“…Such a flow pattern should be observable in the plasma measurements. Nemeth et al (2015) already identified such a flow pattern in the ion measurements of the Cassini spacecraft, but attributed the decreasing azimuthal velocity to sub-corotation intensifying for larger L values, and did not offer an explanation for the observed retrograde motion. In the next section, we revisit these observations in more detail, extending them to latitudinal as well as azimuthal flow patterns and showing how the experimental data support the existence of giant closed field line vortices in the tail lobes.…”
Section: Theorymentioning
confidence: 97%
See 1 more Smart Citation
“…The Saturnian plasma sheet, in particular, was extensively studied during the last decade. Its three‐dimensional structure and its dynamical (periodic and episodic) variability was revealed through multi‐instrumental data analyses (e.g., Arridge et al, ; Carbary et al, ; Cowley & Provan, ; Kellett et al, ; Krupp et al, ; Nemeth et al, ; Sergis et al, , ; Thomsen et al, ; Wilson et al, , ) and modeled by several sophisticated approaches (e.g., Achilleos, Guio, & Arridge, ; Arridge et al, ; Cowley & Provan, ; Jia & Kivelson, ).…”
Section: Introductionmentioning
confidence: 99%